Globalization and the Role of the English Language - Todorova, N.; Todorova, A. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2018)
In the framework of the linguistic approach to understanding the impact of globalization on the humanity, this paper aims to consider the role of the English language in globalization processes. Given the history of English becoming the world’s most widely spoken language, the authors consider possible implications of this fact and overview the current debates and concerns about the role of English and the state of other world languages under conditions of globalization.